(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
In this research many new N-aryl substituted di allylAmins were synthesized [ A1-A2 ] which were Polymerized by free radically mechanism by using Ammonium per sulfate as an initiator at 700C .The new hindered amines as cyclo polymers were characterized by FTIR and H-NMR Spectroscopies ,Physical and chemical properties were measured using TGA and DSC to study the thermal stability of prepared cyclopolymers . These prepared N-aromatic substituted di allylamins cyclopolymers [ A3 - A4 ] were used as antioxidants for lubricant oil . which give high stability when comparing with standard antioxidant . The oxidation stability of base oil with (1% ) additive were examined according to Institute of Petroleum testing method IP280